Keputusan Konsumen Mengkonsumsi Pinang Kering Iris di Kecamatan Kota Kefamenanu Kabupaten Timor Tengah Utara - Agustinus Nubatonis; Elisabeth Ananda Putri Alupan; Achmad Subchiandi Maulana; Umbu Joka; Boanerges Putra Sipayung (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Consumption of areca nut has become a culture of society in the District of Kota Kefamenanu. Sliced dried areca nut is an option for consumption because it can last a long time. Slice dried arecal nut in Kota Kefamenanu sub-district is divided into two types, namely dry iris batu nut and iris dry muda nut. This study aims to analyze the consumer's decision to consume sliced dried areca batu and slice dry areca muda nut in Kota Kefamenanu District. This research was conducted from September to October 2021. The number of samples used in this study was 150. Consumer decisions in Kefamenanu City were analyzed by logistic regression using software Eviews9. The results showed that psychological factors and texture variables had a significant effect on consumer decisions to consume sliced dried areca nut in Kefamenanu City District.